Proteomic insights into seed germination in response to environmental factors. Issue 12 (5th July 2013) - Tan, Longyan; Chen, Sixue; Wang, Tai; Dai, Shaojun
Abstract : Seed germination is a critical process in the life cycle of higher plants. During germination, the imbibed mature seed is highly sensitive to different environmental factors. However, knowledge about the molecular and physiological mechanisms underlying the environmental effects on germination has been lacking. Recent proteomic work has provided invaluable insight into the molecular processes in germinating seeds of Arabidopsis, rice ( Oryza sativa ), soybean ( Glycine max ), barley ( Hordeum vulgare ), maize ( Zea mays ), tea ( Camellia sinensis ), European beech ( Fagus sylvatica ), and Norway maple ( Acer platanoides ) under different treatments including metal ions (e.g. copper and cadmium), drought, low temperature, hormones, and chemicals (gibberellic acid, abscisic acid, salicylic acid, and α‐amanitin), as well as Fusarium graminearum infection. A total of 561 environmental factor‐responsive proteins have been identified with various expression patterns in germinating seeds. The data highlight diverse regulatory and metabolic mechanisms upon seed germination, including induction of environmental factor‐responsive signaling pathways, seed storage reserve mobilization and utilization, enhancement of DNA repair and modification, regulation of gene expression and protein synthesis, modulation of cell structure, and cell defense. In this review, we summarize the interesting findings and discuss the relevance and significance for our understanding of environmental regulation of seed germination.